1986
DOI: 10.1021/jf00068a010
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of the persistent plasticizer chemical bis(2-ethylhexyl) phthalate in cell suspension cultures of wheat (Triticum aestivum L.). Discrepancy from the intact plant

Abstract: Metabolism of the Persistent Plasticizer Chemical Bis(2-ethylhexyl) Phthalate in Cell Suspension Cultures of Wheat (Triticum aestivum L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…in cell culture experiments, it was metabolized rapidly, predominantly to polar /S-D-glucosyl conjugates. The same occurred with mono(2-ethylhexyl) phthalate (Krell and Sandermann, 1986). For phthalic acid, which may be formed from DEHP in soil, it was shown that a significant uptake of UC from the 14C-labeled compound by plants occurred (Dorney et al, 1985).…”
Section: Acknowledgmentmentioning
confidence: 71%
See 2 more Smart Citations
“…in cell culture experiments, it was metabolized rapidly, predominantly to polar /S-D-glucosyl conjugates. The same occurred with mono(2-ethylhexyl) phthalate (Krell and Sandermann, 1986). For phthalic acid, which may be formed from DEHP in soil, it was shown that a significant uptake of UC from the 14C-labeled compound by plants occurred (Dorney et al, 1985).…”
Section: Acknowledgmentmentioning
confidence: 71%
“…This is in line with observations of Kato et al (1980) who did not find any DEHP in several plant species (Chrysanthemum coronarium, Brassica rapa, spinach) grown in DEHP-contaminated soil. Krell and Sandermann (1986) found that DEHP was not taken up into wheat cells when applied to wheat leaves but was partitioned or adsorbed to cuticles, triglyceride droplets, and cell wall components. When DEHP was taken up into plant cells, e.g.…”
Section: Acknowledgmentmentioning
confidence: 99%
See 1 more Smart Citation